In Vitro Regeneration and Establishment of Plantlets in Stem Cultures of Dalbergia latifolia Roxb - Devi, A. M. Sudha; Nataraja, K. (Indian Forester, 1987)
The stem segments of Dalbergia latifolia Roxb. regenerated roots directly on MS medium with an auxin, and shoot buds either directly or through callus formation in presence of a cytokinin. The shoot buds failed to develop roots in situ. The roots were induced from such buds when they were excised and transferred to MS medium with an auxin. The rooted shoot buds were transferred to soil and were maintained successfully.